2003
DOI: 10.1111/j.1432-2277.2003.tb00223.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluvastin therapy affects TAFI concentration in kidney transplant recipients

Abstract: Thrombin activatable fibrinolysis inhibitor (TAFI) is a glycoprotein, linking coagulation and fibrinolysis. Recently, attention has been drawn to the beneficial effects of statins on haemostasis in kidney patients prone to dyslipidaemia and with a high risk of cardiovascular death. The purpose of this study was to assess whether fluvastatin affects TAFI concentration in renal transplant recipients. We evaluated thrombin-antithrombin (TAT) complexes, prothrombin fragments 1 + 2, thrombomodulin, plasminantiplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The mechanism underlying association between elevated plasma TAFI and LDL cholesterol in type 2 diabetic patients remains to be determined. Malyszko et al (18) reported that in hyperlipidemic patients undergoing renal transplantation, treatment with a statin brought about significant decreases in both plasma TAFI and LDL cholesterol, supporting present findings of a positive correlation between TAFI and LDL cholesterol.…”
Section: Pai-1 and Tafi In Diabetes With Mssupporting
confidence: 78%
“…The mechanism underlying association between elevated plasma TAFI and LDL cholesterol in type 2 diabetic patients remains to be determined. Malyszko et al (18) reported that in hyperlipidemic patients undergoing renal transplantation, treatment with a statin brought about significant decreases in both plasma TAFI and LDL cholesterol, supporting present findings of a positive correlation between TAFI and LDL cholesterol.…”
Section: Pai-1 and Tafi In Diabetes With Mssupporting
confidence: 78%
“…Depletion of thyroid hormones leads to a reduced number of LDL receptors in the liver and to decreased biliary excretion of cholesterol resulting in elevated serum LDL. The relationship between LDL cholesterol and TAFI antigen levels have been reported in several studies [30][31][32]. Aso et al [32] found that serum LDL cholesterol is an independent predictor of plasma TAFI levels in type 2 diabetes.…”
Section: Discussionmentioning
confidence: 88%
“…It has been demonstrated that TAFI is expressed in adipocytes, which might explain the association of plasma TAFI concentrations with metabolic disturbances [62,71]. Positive associations between TAFI and low density lipoprotein cholesterol have been noted [48]; accordingly, simvastatin and fluvastatin therapies have been shown to decrease plasma TAFI concentrations [72][73][74]. Finally, decreases in plasma TAFI concentrations have been noted in the case of different diseases of the liver, in keeping with the hepatic site of expression of plasma-derived TAFI [75][76][77], and may or may not correlate with increased plasma fibrinolysis [76,77].…”
Section: Non-genetic Influences On Plasma Tafi Concentrationsmentioning
confidence: 98%